The Effects of Arousal and Approach Motivated Positive Affect on Cognitive Control. An ERP Study - Cudo, Andrzej; Francuz, Piotr; Augustynowicz, Paweł; Stróżak, Paweł (Frontiers in Human Neuroscience, 2018)
A growing body of research has demonstrated that affect modulates cognitive control modes such as proactive and reactive control. Several studies have suggested that positive affect decreases proactive control compared to neutral affect. However, these studies only focused on the valence of affect and often omit two of its components: arousal and approach motivation. Therefore, we designed the present study to test the hypothesis that cognitive control modes would differ as a function of arousal and approach motivated positive affect. In our study, we used an AX-continuous performance task, commonly used to examine shifts in proactive and reactive control. We also used P3b, contingent negative variation (CNV), N2 and P3a components of event-related brain potentials (ERPs) as indicators of the use of cognitive control modes. The findings of the present study demonstrate that approach motivated positive affect modified only P3b and CNV without effects on the N2 and P3a components. However, arousal induced by pictures modified P3b, CNV, and N2 amplitude. Specifically, P3b amplitude was larger, and CNV amplitude was less negative in high than in low-approach motivated affect. By contrast, P3b amplitude was larger, CNV amplitude was more negative, and N2 amplitude was more negative in low than in high-arousal conditions. These ERP results suggest that approach motivated positive affect enhanced proactive control with no effect on reactive control. However, arousal influenced both proactive and reactive control. High arousal decreased proactive control and increased reactive control compared to low arousal. The present study provides novel insights into the relationship between affect, specifically, arousal and approach motivated positive affect and cognitive control modes. Also, our results contribute to explaining the existing discrepancies in previous research.